Do eWOM and Brand Image Drive Purchase Intention of Online Travel Shoppers : A Case Study of Delhi - NCR - Gupta, Ashwerya; Savita, Ubba (Indian Journal of Marketing, 2024)
Purpose : The increasing trend of traveling and the widespread use of the internet have led to a growth in the market for online travel buying. The present study yielded valuable insights into the impact of electronic word of mouth (eWOM) features, both directly and indirectly, on purchase intention for online travel items through brand image. Additionally, the association between eWOM traits and purchase intention is examined, as well as the mediating effect of brand image. Methodology : A systematic survey was created and distributed to 854 internet-savvy participants who frequently purchase vacations online. The PLS-SEM software 3.3.3 was used to carry out the statistical analysis. Additionally, importance-performance matrix analysis, or IPMA, was used to investigate the critical elements involved in determining customer intention. Findings : The study found that eWOM characteristics influence brand perception more so than consumers’ intentions to purchase online travel products. It was also demonstrated that eWOM characteristics were higher even if performance was less relevant. That being said, brand image was not as crucial as performance. Practical Implications : Marketers and decision-makers in the online travel sector should take note of the study’s conclusions since they can significantly improve a brand’s reputation. The results could be used to monitor sentiments and gauge their impact. Originality : The study emphasized the significance of eWOM attributes and brand image for purchase intentions in the context of the developing Indian online travel market. The study used the IPMA, a contemporary PLS-SEM technique, to establish the results.